2016
DOI: 10.2118/179691-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Microfluidic Investigation of the Synergistic Effect of Nanoparticles and Surfactants in Macro-Emulsion-Based Enhanced Oil Recovery

Abstract: Summary Injecting oil-in-water (O/W) emulsions stabilized with nanoparticles (NPs) or surfactants is a promising option for enhanced oil recovery (EOR) in harsh-condition reservoirs. Stability and rheology of the flowing emulsion in porous media are key factors for the effectiveness of the EOR method. The objective of this study is to use microfluidics to (1) quantitatively evaluate the synergistic effect of surfactants and NPs on emulsion dynamic stability and how NPs affect the emulsion proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 64 publications
0
44
0
1
Order By: Relevance
“…The efficiency of wettability change by silica NPs was shown to be enhanced at higher temperatures [20]. Apart from wettability change, silica NPs have also been shown to reduce oil-water interfacial tension thereby improving the mobility of oil phase [27][28][29] and stabilize oil in water emulsions [30][31][32][33] for EOR application. Monfared, et al [34] studied the adsorption of silica NPs on calcite surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of wettability change by silica NPs was shown to be enhanced at higher temperatures [20]. Apart from wettability change, silica NPs have also been shown to reduce oil-water interfacial tension thereby improving the mobility of oil phase [27][28][29] and stabilize oil in water emulsions [30][31][32][33] for EOR application. Monfared, et al [34] studied the adsorption of silica NPs on calcite surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…На сегодняшний день исследовательские группы по всему миру ве-дут лабораторные тестирования технологических жидкостей с содер-жанием наночастиц различных минералов [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] для их применения в МУН и ИДН. Разработанные технологические жидкости с новыми фи-зико-химическими свойствами должны отвечать следующим основным требованиям: экологичность, селективность и экономическая эффек-тивность.…”
Section: The Results Of the Specialists' And Scientists' Researchesunclassified
“…Due to the strong reservoir heterogeneity and fluid channeling, it is reported that the normal water flooding can only produce about 30% of the total reserves of oil 3 . To overcome these difficulties, several EOR techniques have been proposed, including polymer flooding 3–5 , oil-in-water (O/W) emulsions 6,7 and foam displacement 8 . Among these techniques, polymer flooding is considered as one of the most promising technologies 9 .…”
Section: Introductionmentioning
confidence: 99%